Pole plate effected gradient coils design in permanent magnet MRI system. Issue 4 (19th November 2016) - Xu, Yajie; Lopez, Hector Sanchez; Chen, Qiaoyan; Yang, Xiaodong
Abstract: Pole plate in permanent magnet MRI system leads to serious impact on the strength, linearity, and inductance of gradient coils due to the induced current of its pure iron material. In this article, a modified mirror current (MC) model of pole plate based on z gradient coil is established, aiming at improving gradient coil performance. Levenberg‐Marquardt ( LM ) algorithm is applied for the gradient coil optimization with and without constraint of the current density coefficient that determines the coil complexity and structure. With the optimal constraint radius 4.466 and 4.942, the minimum square of gradient field errors are obtained as 3.1991 × 10 − 12 and 3.5711 × 10 − 6 for longitudinal and transverse gradient coils, respectively. Optimization results combining linearity, inductance and field error ameliorate all three parameters prominently comparing with the original MC model, which proves the efficiency of the modified MC model and LM optimization algorithm in gradient coil construction to compensate the pole plate effect.